1969
DOI: 10.1103/physrev.178.168
|View full text |Cite
|
Sign up to set email alerts
|

Momentum-Transfer Cross Sections and Conductivity Ratios for Low-Energy Electrons in He, Ne, Kr, and Xe

Abstract: Conductivity ratios have been measured in weakly ionized afterglows of repetitively pulsed, electrodeless, rf discharges in helium, neon, krypton, and xenon using a microwave resonant cavity (2.7 GHz). Maxwellian electron-energy distributions were obtained at temperatures from 300°K to 10 000°K, as measured with a gated microwave radiometer (4 GHz), Momentumtransfer cross sections for electrons of energy up to 2 eV in neon, krypton, and xenon were determined from the measured conductivity ratios by an iterativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1971
1971
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 27 publications
(10 reference statements)
0
10
0
1
Order By: Relevance
“…σ MT [39] 0.249 Phase shift analysis [43] 0.22 Polarized orbital [44] 0.201 Expt. (condctivity ratio, Sashkatchewan) σ MT [45] 0.20 Expt. (drift velocity, ANU) σ MT [40] 0.24 Expt.…”
Section: Neonmentioning
confidence: 99%
“…σ MT [39] 0.249 Phase shift analysis [43] 0.22 Polarized orbital [44] 0.201 Expt. (condctivity ratio, Sashkatchewan) σ MT [45] 0.20 Expt. (drift velocity, ANU) σ MT [40] 0.24 Expt.…”
Section: Neonmentioning
confidence: 99%
“…7. The cross section of Frost and Phelps (1964) was derived from measurements of drift velocities in pure krypton, while Hoffmann and Skarsgard (1969) used measurements of microwave conductivity ratios. Hunter et al (1987) have suggested that the drift velocity measurements used by Frost and Phelps are in error due to the presence of impurities (Section 2).…”
Section: The Present Kr Momentum Transfer Cross Sectionmentioning
confidence: 99%
“…(14). In fact, such a procedure would be very time consuming, owing to the very long integration time, and we prefer to measure T p by linear interpolation between two temperatures Tstd for which l1y is first negative, then positive.1 5…”
Section: A Microwave Network Noise Contributionmentioning
confidence: 99%